Pengaruh Kedisiplinan, Kepuasan Dan Motivasi Kerja Terhadap Kinerja Dosen Tetap Universitas Katolik Darma Cendika Surabaya - Lilik Indrawati (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2012)
Lecturer is the importance essence of the educational activities primarily related to teaching and learning activities. Without the role of the lecturer, the teachinglearning process will be disrupted even fail. Therefore, in education management, performance or achievements of lecturer’s work should be improved consideringthe challenges of education nowadays is to produce human resources quality that capable is of competing in the era of globalization. In subsequent developments, many opinions said that the performance of lecturer will be very much influencedby attitude and behavior, which include employ discipline, job satisfaction, and work motivation. The above description encourages the writer to conduct a research whether the employ discipline, job satisfaction dan work motivation really affect the performance of lecturers at Darma Cendika Surabaya CatholicUniversity. The research objects to be retrieved is the population of permanent lecturers of Darma Cendika Surabaya Catholic University. There are 32 lecturers. Analysis technique used is multiple regression. From the research results obtained that the performance of lecturers of Darma Cendika SurabayaCatholic University is influenced by three independent variables namely employ discipline variable (X1), job satisfaction variable(X2), and work motivation variable (X3). The value of the adjusted coefficient of determination of 87.9%, means that 87.9% of performance of lecturers of Darma Cendika Surabaya Catholic University influenced the employ discipline variable (X1), jobsatisfaction variable (X2), and work motivation variable (X3), while the remaining balance of 12.1% influenced by other factors is not examined by the author. These three independent variables, namely employ discipline (X1), job satisfaction (X2), and work motivation (X3) affect the performance of lecturers are partially or simultaneously. As a result, the variable of work motivation(X3) is the most dominant variable, which affects significantly the performance of lecturers of Darma Cendika Surabaya Catholic University. The results showed that the performance of lectures of Darma Cendika Surabaya Catholic University are good and very good. On the variable of employ discipline (X1), it should benoticed that the work given to the lecturers of Darma Cendika Surabaya Catholic University should in accordance with ability. On the job satisfaction variable (X2), which need to be considered is the satisfaction of a job as a lecture of Darma Cendika Surabaya Catholic University. It has elements of satisfied or proud being a lecturer of Darma Cendika Surabaya Catholic University. On workmotivation variable (X3), the physiological needs (physiological), such as food, drink, shelter, rest and wants to get a job that provides adequate wages is the main point. In the variable of lecturer’s performance (Y), what is need to be paid attention is lecturer’s research for each year.